Pengelolaan Olimpiade Olahraga Siswa Nasional Sekolah Dasar Di Kota Surakarta - Rohani, Badri, Prof. Dr. Abdul Ngalim, M.M, M.Hum, Dr. Sumardi, M.Si (2016)
This study have three aims: 1) The results of the management of the National Students Sports Olympiad Elementary School, 2) management planning of the National Students Sports Olympiad Elementary School, 3) management process of the National Students Sports Olympiad Elementary School in Surakarta City. This research is qualitative research with etnography research design. Data was collected by observation, interview, and documentation. Data analysis consists of three components: data reduction, data display, and drawing conclusions and verification. Results of this research there are three things about: 1) Since held in 2008, state elementary school students in Surakarta just reach achievement in 2010 at the Southeast Asia level. Head of Curriculum Section of Education and Sports in Surakarta City coordinating with teachers Sports 1-2 months before follow O2SN (National Students Sports Olympiad). 2) At the time dimension of planning is often done incidentally. Schools make the selection of potential students represent competition in O2SN. Coaching is still in discourses and appeals, there has been no real guidance. Schools themselves that preparing to follow O2SN. Exercises in preparation for follow O2SN done gradually. Department of Education and Sports providing assistance complete equipment for schools. 3) Management facing O2SN from Department of Education Youth and Sports in Surakarta City are decentralized but centralized control is carried out on each unit implementing each technique of sub districts. School always assess student achievement, then recommend to the club in the Surakarta City.